2022
DOI: 10.1038/s41435-022-00180-w
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell immune repertoire sequencing of B and T cells in murine models of infection and autoimmunity

Abstract: Adaptive immune repertoires are composed by the ensemble of B and T-cell receptors within an individual, reflecting both past and current immune responses. Recent advances in single-cell sequencing enable recovery of the complete adaptive immune receptor sequences in addition to transcriptional information. Here, we recovered transcriptome and immune repertoire information for polyclonal T follicular helper cells following lymphocytic choriomeningitis virus (LCMV) infection, CD8+ T cells with binding specifici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Of note this subset of murine ASCs was entirely absent in the CNS of naive mice and in the widely used MOG 35-55 - and rMOG 1-125 -induced EAE mouse models (Yermanos, Neumeier, et al 2021; Shlesinger et al 2022). While minor clonal expansion of B cells was present in both naive and EAE conditions, the recovered B cells demonstrated either naive or memory B cell phenotypes and entirely lacked ASC gene signatures, class-switching, contemporary clonal variants, and expression of cell cycle and proliferation genes in contrast to MS patients as found in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Of note this subset of murine ASCs was entirely absent in the CNS of naive mice and in the widely used MOG 35-55 - and rMOG 1-125 -induced EAE mouse models (Yermanos, Neumeier, et al 2021; Shlesinger et al 2022). While minor clonal expansion of B cells was present in both naive and EAE conditions, the recovered B cells demonstrated either naive or memory B cell phenotypes and entirely lacked ASC gene signatures, class-switching, contemporary clonal variants, and expression of cell cycle and proliferation genes in contrast to MS patients as found in this study.…”
Section: Discussionmentioning
confidence: 97%
“…This finding supports a sustained 'inflationary T cell expansion' phenomenon that has been described in the context of chronic lymphocyte choriomeningitis virus (LCMV) infections. 63 Immunosenescence associated B cell alterations, governed by hormonal and sex chromosome associated factors, accompany aging in a sex differential manner. 25 Indeed, immune profiling of aging mice confirmed the higher frequency of ABCs in aging female mice compared to their male counterparts under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports a sustained ‘ inflationary T cell expansion ’ phenomenon that has been described in the context of chronic lymphocyte choriomeningitis virus (LCMV) infections. 63…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate several use cases of the ePlatypus computational ecosystem, we integrated and analyzed multiple single-cell transcriptomes and immune receptor repertoires across different disease conditions, viral infections, and vaccination studies. We directly downloaded murine T cell repertoires from previously published datasets containing both CD4 and CD8 T cells from conditions such as acute and chronic viral infections (Khatun et al, 2021; Kuhn et al, 2022; Merkenschlager et al, 2021; Shlesinger et al, 2022), homeostatic aging (Yermanos, et al, 2021) and experimental autoimmune encephalomyelitis (Shlesinger et al, 2022) (Table S2). Following transcriptional integration with Harmony (Korsunsky et al, 2019), which aims to reduce batch effects across different datasets, we visualized all cells using uniform manifold approximation projection (UMAP) (Figure S11A, S11B).…”
Section: Mainmentioning
confidence: 99%
“…Next, we used ePlatypus to investigate whether similar transcriptional heterogeneity could be detected for B cells present in the PlatypusDB. Multiple datasets derived from murine models of infection, immunization and autoimmune disease (Agrafiotis et al, 2021; Mathew et al, 2021b; Neumeier et al, 2021; Shlesinger et al, 2022; Yewdell et al, 2021) were integrated as previously described (Table S2). Transcriptional clustering suggested that common B cell clusters were present across multiple datasets (Figure S14A), which exhibited varying expression levels of markers relating to antibody secretion and B cell differentiation (e.g.…”
Section: Mainmentioning
confidence: 99%